The pro-poor research and development model - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The model is designed to generate a more focused research agenda by targeting areas for potential high impact, identifying needs and opportunities, and recognizing the need for flexibility to take projects to scale, measure their impacts, and adjust their lessons to research projects and priorities. It also incorporates analyses of impact pathways to better understand how research outputs are taken up (or not) and how they are (or should be) used to promote positive results. Its five stages, organized in a continuous cycle with each step informing the development of the next one, include targeting, needs and opportunities assessment, research, scaling out, and impact assessment.